The influence of the trajectory of obesity indicators on the age of pubertal onset and pubertal tempo in girls: A longitudinal study in Chongqing, China - Xuan Xi; Di Wu; Di Wu; Wenyi Wu; Yuanke Zhou; Qin Zhang; Yujie Wang; Hong Wang; Qin Liu (Frontiers Media S.A., 2023)
ObjectiveThis study aims to explore the influence of the trajectory of obesity indicators on the onset age of different pubertal development characteristics and pubertal tempo among girls.MethodsOur longitudinal cohort study recruited 734 girls at baseline in May 2014 from a district of Chongqing and followed them at 6-month intervals. Data were available from baseline to the 14th follow-up with a full record of height, weight, waist circumference (WC), breast development, pubic hair, and armpit hair development, as well as the age of menarche. The Group-Based Trajectory Model (GBTM) was fitted for the optimum trajectory of the body mass index (BMI), WC, and waist-to-height ratio (WHtR) of girls before the pubertal onset and menarche. The ANOVA and multiple linear regression model were conducted to analyze the influence of the trajectory of obesity indicators on the onset age of different pubertal development characteristics and pubertal tempo in girls.ResultsCompared with the healthy (gradual BMI increase) group before pubertal onset, the overweight (persistent BMI increase) group has an earlier onset age of breast development (B: −0.331, 95%CI: −0.515, −0.147) and pubic hair development (B: −0.341, 95%CI: −0.546, −0.136). The B2-B5 development time was shorter in girls in the overweight (persistent BMI increase) group (B: −0.568, 95%CI: −0.831, −0.305) and the obese (rapid BMI increase) group (B: −0.328, 95%CI: −0.524, −0.132). The age of menarche was earlier, and the B2-B5 development time was shorter in girls in the overweight (persistent BMI increase) group than in girls in the healthy (gradual BMI increase) group before menarche (B: −0.276, 95%CI: −0.406, −0.146; B: −0.263, 95%CI: −0.403, −0.123). Girls with high WC (rapid WC increase) before menarche had an earlier age of menarche than normal WC (gradual WC increase) (B: −0.154, 95%CI: −0.301, −0.006), and the B2-B5 development time was shorter in girls in the overweight (gradual WHtR increase) group than in girls in the healthy (persistent WHtR increase) (B: −0.278, 95%CI: −0.529, −0.027) group.ConclusionAmong girls, overweight and obesity (BMI scale) before pubertal onset can not only influence pubertal onset age but also accelerate B2-B5 pubertal tempo. Overweight (BMI scale) and high WC before menarche also have an impact on the age of menarche. Overweight (WHtR scale) before menarche is significantly associated with B2-B5 pubertal tempo.